Bahasa dan Pendidikan Karakter Dalam Pandangan Ki Hadjar Dewantara (Perspektif Teori Kritis Habermas) - Acetylena, Sita (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2018)
Resistance Ki Hadjar Dewantara in pioneering independence through a political movement or through character-based education is done by making the language as a fulcrum ofpengthe strugglemotion. Language is used as a tool to instill national character and language as a means to achieve independence discourse. Therefore, the purpose of this research is to know and understand Ki Hadjar Dewantara thinking about language and character education in view of Critical Theory Habermas. Habermas critical theory is a critical theory of communicative paradigm. In addition, to know how the language and character education undertaken Ki Hadjar Dewantara affects the movement's struggle for independence in Indonesia so as to become a sovereign state and is able to align with other nations in the world. Language and Character Education by Ki Hadjar Dewantara is very substantial for the existence and civilization of a nation. Speaking of character education the existence of a nation that is sovereign, independent, and self-sufficient should be based on a solid spiritual foundation that is reflected in the values of the character of the nation, especially character